« T’es intelligent pour un arabe ! »Auto-ethnographie d’un corps colonisé - Marc Jahjah (Itinéraires)
In this paper, I document the processes of fetishization and racial typification personally experienced from a dating gay device (Grindr). I particularly ask why bodies of certain people, clearly perceived as “arab”, are subject to narration and appropriation, which literally transform them into the occurrence of a race, or an object of consumption, aligned with problematic sexual scripts, clearly inherited from colonization. This process, which can combine racialized and white people in asymmetrical teams, is identified, analyzed and narrated from a theoretical and methodological prism where anthropology, sociology, communication sciences meet feminist, decolonial and queer epistemologies.